2000
DOI: 10.1053/joca.1999.0321
|View full text |Cite
|
Sign up to set email alerts
|

FrzB-2: a human secreted frizzled-related protein with a potential role in chondrocyte apoptosis

Abstract: These data suggest that FrzB-2 may play a role in apoptosis and that the expression of this protein may be important in the pathogenesis of human OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 27 publications
0
47
0
1
Order By: Relevance
“…These data indicate that sFRP-4 has phosphatonin-like properties, promoting phosphaturia and hypophosphatemia, and may therefore control bone mineralization. Finally, James et al [2000] have reported that sFRP-4 is highly expressed in chondrocytes from patients with sFRP-1 Controls Osteoblast and Osteocyte Apoptosisosteoarthritis, while its expression is negligible in cells from normal cartilage. Moreover, the authors observed a correlation between sFRP-4 expression and chondrocyte apopotosis.…”
Section: Discussionmentioning
confidence: 98%
“…These data indicate that sFRP-4 has phosphatonin-like properties, promoting phosphaturia and hypophosphatemia, and may therefore control bone mineralization. Finally, James et al [2000] have reported that sFRP-4 is highly expressed in chondrocytes from patients with sFRP-1 Controls Osteoblast and Osteocyte Apoptosisosteoarthritis, while its expression is negligible in cells from normal cartilage. Moreover, the authors observed a correlation between sFRP-4 expression and chondrocyte apopotosis.…”
Section: Discussionmentioning
confidence: 98%
“…Inhibition of Wnt proteins promotes programmed cell death in different types of cancer cells (50,51). In human OA cartilage, FrzB-2 is highly expressed and is associated with chondrocyte apoptosis (52). In Col2a1-ICAT-transgenic mice in which ␤-catenin signaling is selectively blocked in chondrocytes, apoptosis is increased (27).…”
Section: Discussionmentioning
confidence: 99%
“…OA cartilage displays signs of Wnt/catenin activation and expresses FRP (7,32,33). Ectopic canonical Wnt signaling leads to enhanced ossification and suppression of chondrocyte formation (34).…”
Section: Discussionmentioning
confidence: 99%